Characterization of SiO2 Nanoparticles by Single Particle - Inductively Coupled Plasma – Tandem Mass Spectroscopy - Pereira Leite, Diego; Bolea-Fernandez, Eduardo; Rúa Ibarz, Ana; Resano, Martín; Vanhaecke, Frank; Aramendía, Maite (Jornada de Jóvenes Investigadores del I3A, 2017)
This work uses the tandem ICP-MS (ICPMS/MS) for obtaining interference-freeconditions to characterize SiO2 nanoparticles ranging between 80 and 400nm. These NPs have been detected and accurately characterized. For SiO2 NPs >100 nm, it was possible to provide accurateresults in a straightforward way, as theirsignal distributions are well resolved fromthat of the background.